RESILIENSI PADA KARYAWAN PABRIK DI KOTA X - Purnomosidi, Faqih; Patria, Helvetia Fajar (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
Resilience is an individual's effort to be able to stay on a positive path in facing challenges or obstacles that can create stress. Resilience can be done by everyone, including factory employees. There are many actions that factory workers can take to avoid work stress, one of which is maximizing resilience. The aim of this research is to explain the picture of resilience in factory employees The method used is a qualitative descriptive method with data collection using interviews. The informants in this research were 4 people who were working in a factory. The main result of this research is that the majority of employees from various factories in Boyolali who were sources in this research already have a good level of resilience. This can be explained that every employee who is under stress does not immediately have negative emotions. Apart from that, employees are able to manage stress well, this is because the regulations that employees have are relatively good